2020
DOI: 10.5365/wpsar.2018.9.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of individuals with tuberculosis in an urban, poor population in Osaka City, Japan — a case-control study

Abstract: Objective: To identify individual characteristics related to the development of pulmonary tuberculosis (PTB) among residents in the Airin area (Airin), Osaka City, Japan. Methods: We conducted a retrospective case-control study of individual characteristics potentially related to the development of PTB by comparing PTB patients and residents without tuberculosis (TB) in Airin. The following binominal data of characteristics were compared: age (<65 or >65); body mass index (BMI) (<18.5 or >18.5);di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A final meta-analysis with studies recruiting patients with latent TB revealed no significant association for one cohort study and a weak association for 12 cross-sectional studies [16]. Compared to these previous systematic reviews, we included over 10 additional articles and used a very rigorous methodology including calculating effect estimates of primary data from included studies and taking into account a wide range of confounding factors of the association between DM and TB listed in the articles included [35,43,45,48,53,58,61,62,64,67,70,73,77,79]. Little is known about the biological mechanisms that underlie a high risk of developing TB in patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…A final meta-analysis with studies recruiting patients with latent TB revealed no significant association for one cohort study and a weak association for 12 cross-sectional studies [16]. Compared to these previous systematic reviews, we included over 10 additional articles and used a very rigorous methodology including calculating effect estimates of primary data from included studies and taking into account a wide range of confounding factors of the association between DM and TB listed in the articles included [35,43,45,48,53,58,61,62,64,67,70,73,77,79]. Little is known about the biological mechanisms that underlie a high risk of developing TB in patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…Japan is a moderately endemic country for TB with a TB notification rate of 13.3 per 100 000 people in 2017 [ 12 ]. Therefore, in Japan, it is recommended to administer the BCG vaccine (particularly for the BCG Tokyo-172 strain) to infants aged 5 to 8 months due to its high efficiency in preventing the development of TB and low complication rate [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As diabetes mellitus was not shown to be associated with TB disease in a previous case–control study in Airin in 2015–2018, ( 15 ) this was analysed separately from other comorbidities.…”
Section: Methodsmentioning
confidence: 99%